IMPLEMENTATION OF THE MUBASYAROH METHOD FOR THE ARABIC LANGUAGE CLASS PROGRAM IN INCREASING VOCABULARY AT THE ELEMENTARY SCHOOL OF THE FUTURE ISLAMIC SCHOOL PEKANBARU - Amida Fazuhrah; Hakmi Wahyudi (UIR Press, 2023)
Abstract The Mubasyarah method is an alternative to improve students' mastery or memorization of Arabic vocabulary. The deliberation method is also applied at the elementary school of the future Islamic School Pekanbaru in the Arabic class program every Tuesday morning. This study aims to determine the implementation of the deliberation method in Arabic language class programs for increasing vocabulary. The method used by researchers is a descriptive analysis method with a qualitative approach. The data collection techniques used are observation, interviews, and documentation. The results of the interviews show that the purpose of using the deliberation method in the language class program at the elementary school of the future Islamic school Pekanbaru is so that students can master and be motivated again to know simple Arabic vocabulary. In practice, the teacher prepares vocabulary related to the material, then reads the text followed by students repeatedly, and the teacher justifies that the students' pronunciation is still wrong. Evaluation of the Arabic class program with the Mubasyarah Method is carried out by giving individual students an assessment in the form of an oral test. Constraints in the Arabic language class program with the deliberation method that students feel are that they have difficulty memorizing the many, long, and difficult words. Meanwhile, the constraints felt by the teacher were that she felt difficulty maintaining order, consistent enthusiasm, and different backgrounds and EQs among students. Keywords: Language Program, Deliberation Method, Vocabulary.